Phylogeny and morphology of Lasiodiplodia species associated with Magnolia forest plants - Nimali I. de Silva (2020)
© 2019, The Author(s). Two new species of Lasiodiplodia (Lasiodiplodia endophytica and Lasiodiplodia magnoliae) are described and illustrated from Magnolia forests in Yunnan, China. Endophytic and saprobic Lasiodiplodia pseudotheobromae and endophytic L. thailandica are new records from this host. The internal transcribed spacers (ITS), part of the translation elongation factor-1α (tef1) and partial β-tubulin (tub2) sequence data were analyzed to investigate the phylogenetic relationships of the new species with other Lasiodiplodia species. Lasiodiplodia magnoliae is phylogenetically sister to L. mahajangana and L. pandanicola but morphologically distinct from L. mahajangana in having larger conidia. Lasiodiplodia endophytica is most closely related to L. iraniensis and L. thailandica and the three species can be distinguished from one another by 2 base pair differences in ITS and three or four base pair differences in tef1. The new collections suggest that Magnolia forest plants are good hosts for Lasiodiplodia species with endophytic and saprobic life-styles.